Evaluation On The Effects Of Nodrainageboundary Condition To The Groundwater Pressure Surrounding The Natm Permanent Cast In-Situ Tunnel Lining - Goh, Chin Ong (2019)
Urbanisation of city and urban area has resulted in urging needs for the construction of new water resources for industrial and residential area. Raw water transfer tunnel is one of the solutions for this problem, as it can transfer water from region with abundant water to water scarcity regions. Tunnelling is a challenging task as there are many uncertainties involved during the construction, especially under moderate to high overburden. Thus, tunnel groundwater flow prediction is crucial during design stage of primary and secondary tunnel lining under the drained or no-drainage boundary conditions in order to minimize the subsidence damage, risk of the tunnel instabilities and environmental impacts. In this study, the parametric study model is developed according to the input of engineering properties data and geological conditions using finite element method (FEM). Besides, a FEM model also carried out to compare with concrete gain strength curve. From the developed hydrostatic graph, the evaluation is done based on the pore water pressure. Additionally, comparison between real instrumentation reading and numerical result is carried out based on tunnel displacement. The effects of groundwater load that control the behaviour of tunnel under different boundary condition were determined. From the analyses, the water load on tunnel lining will decrease if drain condition boundary condition of tunnel lining is provided. For deep excavated tunnel under high groundwater load, the recharge of groundwater will induce cracking of concrete if provided concrete early gain strength is insufficient. The understanding of tunnel lining boundary condition that control the behaviour of moderate to deep tunnel allow engineer to make better preparation or mitigations to overcome the unfavourable geological condition that will occur during the tunnel construction.